2013
DOI: 10.1021/nl400223v
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Nanoparticle Decorating Graphite Felt as a High-Performance Electrode for an All-Vanadium Redox Flow Battery

Abstract: Employing electrolytes containing Bi(3+), bismuth nanoparticles are synchronously electrodeposited onto the surface of a graphite felt electrode during operation of an all-vanadium redox flow battery (VRFB). The influence of the Bi nanoparticles on the electrochemical performance of the VRFB is thoroughly investigated. It is confirmed that Bi is only present at the negative electrode and facilitates the redox reaction between V(II) and V(III). However, the Bi nanoparticles significantly improve the electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
281
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(299 citation statements)
references
References 21 publications
14
281
4
Order By: Relevance
“…There are several popular strategies reported in the literature including oxidation of the active material, and/or the addition of electrocatalytic nanoparticles for more facile kinetics. 38,39 Nevertheless, the presence of pronounced redox peaks demonstrates the utility of MWCNTs as the conductive material for redox electrolytes.…”
Section: Methodsmentioning
confidence: 99%
“…There are several popular strategies reported in the literature including oxidation of the active material, and/or the addition of electrocatalytic nanoparticles for more facile kinetics. 38,39 Nevertheless, the presence of pronounced redox peaks demonstrates the utility of MWCNTs as the conductive material for redox electrolytes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, MWCNTs [5], graphene nanosheets and carbon nanofibers [6,7], functionalization of carbon surface as N-and Ocontaining groups [8], metals such as Pt [6], Ir [9] and Bi [10] and metal oxides Mn 3 O 4 [11,12], WO 3 [13,14], TiO 2 [15], CeO 2 [16], PbO 2 [17], and Nb 2 O 5 [18] were deposited onto the CF supports to prepare modified electrodes. However, although all this research demonstrated an improvement in electrochemical kinetics, the enhanced power density is rarely discussed in the literature as a complementary performance evaluation to the charge/discharge experiments.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The redox reactions of different vanadium species have displayed reversibility and high activity on carbon based electrodes. Moreover, Li et al discovered the catalytic effects of bismuth nanoparticles on V(II)/V(III) [51] and of niobium oxide nanorods on both V(II)/V(III) and V(IV)/V(V) [52], which have been shown to further enhance the energy efficiency of the VRB by more than 10 %.…”
Section: All Vanadium Redox Flow Batteriesmentioning
confidence: 99%